Modulation of potassium channels inhibits bunyavirus infection - Hover, Samantha; King, Barnabas; Hall, Bradley; Loundras, Eleni-Anna; Taqi, Hussah; Daly, Janet M.; Dallas, Mark; Peers, Chris; Schnettler, Esther; McKimmie, Clive; Kohl, Alain; Barr, John N.; et al. (American Society for Biochemistry and Molecular Biology, 2015)
Bunyaviruses are considered to be emerging pathogens facilitated by the segmented nature of their genome that allows reassortment between different species to generate novel viruses with altered pathogenicity. Bunyaviruses are transmitted via a diverse range of arthropod vectors, as well as rodents, and have established a global disease range with massive importance in healthcare, animal welfare and economics. There are no vaccines or anti-viral therapies available to treat human bunyavirus infections and so development of new anti-viral strategies is urgently required. Bunyamwera virus (BUNV; genus Orthobunyavirus) is the model bunyavirus, sharing aspects of its molecular and cellular biology with all Bunyaviridae family members. Here, we show for the first time that BUNV activates and requires cellular potassium (K+) channels to infect cells. Time of addition assays using K+ channel modulating agents demonstrated that K+ channel function is critical to events shortly after virus entry but prior to viral RNA synthesis/replication. A similar K+ channel dependence was identified for other bunyaviruses namely Schmallenberg virus (Orthobunyavirus) as well as the more distantly related Hazara virus (Nairovirus). Using a rational pharmacological screening regimen, twin-pore domain K+ channels (K2P) were identified as the K+ channel family mediating BUNV K+ channel dependence. As several K2P channel modulators are currently in clinical use, our work suggests they may represent a new and safe drug class for the treatment of potentially lethal bunyavirus disease.